4
$\begingroup$

Question: Let $G$ be a group. Prove that $Z(G)$ is a subgroup of $G$.

If I want to show that $Z(G)$ is a subgroup of $G$ that means I have to show that it is closed under group operation?

Here is my attempt.

Let $a,b$ be elements in $Z(G)$ and $x$ be an element in $G$. Then $ax=xa$ which is under group multiplication commutative and under inverse $(a^{-1}) x=x(a^{-1})$. And hence $(a^{-1})bx= (a^{-1})xb=x (a^{-1})b$ which is under group operation so $(a^{-1}),b$ are elements in $Z(G)$ thus a subgroup of $G$.

Really appreciate if anyone can help me by directing me if my attempt is not good. Thanks in advance.

$\endgroup$
1
  • 1
    $\begingroup$ You are trying the use the fact that for $\varnothing \ne S \subset G$, $S$ is a subgroup of $G$ iff $a, b \in S \Rightarrow a^{-1}b \in S$, right? Looks like you got it to me, save for the typo " . . . so $(a^{-1}),b$ are elements i $Z(G)$ . . . "; shouldn't it read "$(a^{-1})b$" instead of "$(a^{-1}),b$"? (No comma after "$(a^{-1})$".) $\endgroup$ May 2, 2014 at 5:39

2 Answers 2

6
$\begingroup$

You need to show that $Z(G)\leq G$.

  1. First of all clearly $1\in Z(G)$ since $1x=x1$ for all $x\in G$.

  2. Let $a,b\in Z(G)$ then $ax=xa$ and $bx=xb$ for all $x\in G$. Then $(ab)x=a(bx)=a(xb)=x(ab)$ so $ab\in Z(G)$.

  3. If $a\in Z(G)$ consider its inverse $a^{-1}$ in $G$. Since $ax=xa$ for all $x\in G$ we have that $a^{-1}(ax)a^{-1}=a^{-1}(xa)a^{-1}$ so $xa^{-1}=a^{-1}x$ for all $x\in G$ namely $a^{-1}\in Z(G)$.

$\endgroup$
1
  • $\begingroup$ just a question, will it be necessary if the definition of a "center of the group" be considered? that is: Z(G)={g element of G | xg=gx for all x element of G} $\endgroup$
    – Sai82
    May 2, 2014 at 6:23
5
$\begingroup$

While you can do this easily by checking the conditions for a subgroup, there is a somewhat easier approach using some general facts. The set of permutations of$~G$ (that is bijections $G\to G$) is a group under function composition (this is true for any set), call it $P(G)$. Define a map $\def\ad{\operatorname{ad}}\ad:G\to P(G)$ by $\ad(g)=(h\in G\mapsto ghg^{-1})$. To see that actually $\ad(g)\in P(G)$ for all$~g\in G$, that is that $\ad(g)$ is always bijective, it suffice to check that $\ad(g^{-1})$ is the inverse map of $\ad(g)$ by a computation similar to what follows. Now show that $\ad$ is a morphism of groups, that is $\ad(g_1g_2)=\ad(g_1)\circ\ad(g_2)$ for all $g_1g_2$. One has $\ad(g_1g_2)=(h\in G\mapsto g_1g_2h(g_1g_2)^{-1})$, whose final expression can be written as $g_1g_2hg_2^{-1}g_1^{-1}$, which is easily checked to be equal to $\ad(g_1)(\ad(g_2)(h))$, as required.

Now to conclude, check that $\def\id{\operatorname{id}}\ker\ad=\{\, g\in G\mid \ad(g)=\id\,\}=\{\, g\in G\mid \forall h\in G:\ad(g)(h)=h\,\}$ is equal to $\{\, g\in G\mid \forall h\in G:ghg^{-1}=h\,\}=Z(G)$. But then $Z(G)$ like any kernel, is a subgroup, even better a normal subgroup. (It is actually even better, namely a characteristic subgroup, but that does not follow as easily from the argument given.)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.